'Next Generation Youth Well-being Study:' understanding the health and social well-being trajectories of Australian Aboriginal adolescents aged 10–24 years: study protocol. Issue 3 (12th March 2019) - Gubhaju, Lina; Banks, Emily; Ward, James; D'Este, Catherine; Ivers, Rebecca; Roseby, Robert; Azzopardi, Peter; Williamson, Anna; Chamberlain, Catherine; Liu, Bette; Hotu, Cheri; Boyle, Jacqueline; et al.
Abstract : Introduction: Australian Aboriginal and/or Torres Strait Islander (hereafter referred to as 'Aboriginal') adolescents (10–24 years) experience multiple challenges to their health and well-being. However, limited evidence is available on factors influencing their health trajectories. Given the needs of this group, the young age profile of the Aboriginal population and the long-term implications of issues during adolescence, reliable longitudinal data are needed. Methods and analysis: The 'Next Generation: Youth Well-being Study' is a mixed-methods cohort study aiming to recruit 2250 Aboriginal adolescents aged 10–24 years from rural, remote and urban communities in Central Australia, Western Australia and New South Wales. The study assesses overall health and well-being and consists of two phases. During phase 1, we qualitatively explored the meaning of health and well-being for adolescents and accessibility of health services. During phase 2, participants are being recruited into a longitudinal cohort. Recruitment is occurring mainly through community networks and connections. At baseline, participants complete a comprehensive survey and undertake an extensive age relevant clinical assessment. Survey and clinical data will be linked to various databases including those relating to health services; medication; immunisation; hospitalisations and emergency department presentations; death registrations; education; child protection and corrective services. Participants will receive follow-up surveys approximately 2 years after their baseline visit. The 'Next Generation' study will fill important evidence gaps by providing longitudinal data on the health and social well-being of Aboriginal adolescents supplemented with narratives from participants to provide context. Ethics and dissemination: Ethics approvals have been sought and granted. Along with peer-reviewed publications and policy briefs, research findings will be disseminated via reports, booklets and other formats that will be most useful and informative to the participants and community organisations.